Neighbors of registered sex offenders: a qualitative analysis of their lived experiences - Beshears, Michelle L. (International journal of law, crime and justice, 2017)
The purpose of this qualitative phenomenological study was to explore the lived experiences and perceptions of those individuals who live next to or in the same neighborhood (area) as a registered sex offender (RSO) in Arkansas. The themes were safety of children, personal knowledge about the offender and or offense, extra precautions, perceptions about the notification process, and effect on lifestyle. The 20 participants were accepting of the situation, but expressed concern and the need to function rationally and with caution, particularly in terms of children. Conclusions also included the need to assess risk levels in terms of recidivism, registration requirements, and RSO policy effectiveness and providing accurate offender information.